Principal Managerial Performance and Its Relationship with Organizational Culture, Personality, Job Satisfaction, and Decision Making in Indonesian Schools - Fiqra Muhamad Nazib; Bibin Rubini; Widodo Sunaryo (Immortalis Journal of Interdisciplinary Studies, 2026)
This study aims to analyze the relationship between principal managerial performance and organizational culture, personality, job satisfaction, and decision making simultaneously in the context of Indonesian schools. A quantitative correlational design was employed, involving school principals and teachers as respondents, selected through probability sampling. Data were collected using Likert-scale questionnaires and analyzed using linearity tests and multiple regression to examine relationships among the variables. The results indicate that all variables have significant linear relationships. Organizational culture and personality positively influence job satisfaction and decision-making effectiveness, which in turn affect principal managerial performance. These findings underscore the importance of developing a supportive organizational culture and strengthening personal characteristics to enhance school leadership effectiveness. The study provides theoretical contributions to educational management literature and practical implications for improving school management quality.